Studies of Tillage-Fertility on Pearl Millet in Sandy Arid Plains of Rajasthan - Singh, S D; Singh, R C; Vyas, D L; Misra, D K; Bhati, N S (Annals of Arid Zone, 2016)
Plough-plant’ gave yield as good as other tillage methods, saved Rs 39 to 83 per ha, and thus finds a place in sandy arid plains of Rajasthan. Application of farmyard manure to supply 11.2 and 22.4 kg N per ha increased the grain yield over the control by 60, and 100 kg per ha. The corresponding responses to N with ammonium sulphate were 100, and 130 kg grain per ha. Ammonium sulphate on equal N basis gave higher yield and profit. Its most profitable rate at assumed prices of Rs 80 per q of pearl millet and Rs 2 per kg of N was 11.5 kg N per ha at which the predicted response was 128 kg and the profit Rs 66. The "minimum rate" of N advocated for average dryland grower was 10 kg per ha at which the returns per rupee spent on fertilizer would be Rs 38.2.